Online communication amongst student during pandemic : a Malaysian and Turkish case study - Fatimah Abdul Razak; Fatien Amierah Zailani; Yalcin, G Cigdem (Penerbit Universiti Kebangsaan Malaysia, 2022)
Online learning is the new norm suddenly imposed on many of us in response to the Covid-19 pandemic. Online communication is crucial for students to be actively involved in the class, not just to communicate with the educators but also to communicate amongst themselves in forming communities of learning typically created through physical classes in pre-Covid-19 times. We created questionnaires through Google Form pertaining to online communication amongst students in both Malay and Turkish languages. While Malaysia has a rich cultural structure with a wide variety of ethnic origins, Turkey acts as a bridge between the European and Asian continents at the western end of the Asian continent. In this study, we consider the geographies of different cultural structures in order to investigate communication behaviors of students in response to the transformation of higher education to online only during Covid-19. The data from the questionnaire is analyzed to highlight communication platforms utilized by students during the pandemic. Although there are differences in both studies of Malaysian and Turkish students in terms of participant number and their year of study, the similarities of online communication platforms preferred by many students such as WhatsApp and Instagram stand out. Interestingly, we see that male students, both Malaysian and Turkish, use more varied and diverse forms of online communications platforms. Additionally, more female students from Turkey are shown to communicate face-to-face with their friends compared to their male counterparts.